2017
DOI: 10.1021/acsomega.7b00801
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Protein Stability of Two Naturally Occurring Thiopurine S-Methyltransferase Variants: Biophysical Characterization of TPMT*6 and TPMT*8

Abstract: Thiopurine S-methyltransferase (TPMT) is a polymorphic enzyme involved in the metabolism and inactivation of thiopurine substances administered as immunosuppressants in the treatment of malignancies and autoimmune diseases. In this study, the naturally occurring variants, TPMT*6 (Y180F) and TPMT*8 (R215H), have been biophysically characterized. Despite being classified as low and intermediate in vivo enzyme activity variants, respectively, our results demonstrate a discrepancy because both TPMT*6 and TPMT*8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that an amino acid shift can give rise to various effects in the TPMT protein [34,35]. Amino acid Y166 is part of the Y166-D151-Y180 hydrogen bonding network in the TPMT protein core [36] and is important for the stabilization of the protein, which also is shown by the lower thermal denaturation temperature observed for TPMT*44 compared to TPMTwt in the presence of SAM (Fig. 6D).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies have shown that an amino acid shift can give rise to various effects in the TPMT protein [34,35]. Amino acid Y166 is part of the Y166-D151-Y180 hydrogen bonding network in the TPMT protein core [36] and is important for the stabilization of the protein, which also is shown by the lower thermal denaturation temperature observed for TPMT*44 compared to TPMTwt in the presence of SAM (Fig. 6D).…”
Section: Discussionmentioning
confidence: 64%
“…6D). The observed decreased stability for other SNPs causing amino acid shifts in this region is explained by causing a shortened protein half-life in vivo due to increased degradation, as investigated and discussed by Wennerstrand et al [36]. It is very likely that the reason for the loss of enzymatic activity in vivo as well as decreased stability during thermal denaturation in vitro for TPMT*44 is due to the localization of the variant in the hydrogen bonding network.…”
Section: Discussionmentioning
confidence: 88%
“…When comparing all four variants, recombinant TPMT*44 (p.Y166C) was shown to have the lowest T m . The decreased thermal stability of TPMT*44 was probably due to disruption of the hydrogen bonding network in the TPMT core involving Y166‐D151‐Y180, which may result in increased degradation and thereby a shortened protein half‐life in vivo 29 . In most of the so far studied TPMT alleles in which SNPs are found within the exons of the TPMT gene, a single amino acid substitution of the TPMT enzyme disturbs the enzyme structure and stability 29‐31 .…”
Section: Resultsmentioning
confidence: 99%
“…29 In most of the so far studied TPMT alleles in which SNPs are found within the exons of the TPMT gene, a single amino acid substitution of the TPMT enzyme disturbs the enzyme structure and stability. [29][30][31] The low TPMT enzyme activity in defective TPMT allele is thereby commonly due to decreased quantities of TPMT enzyme, and for several TPMT alleles, correlation between enzyme levels and activity has been shown. 10,32 Increased aggregation formation and proteolysis are also consequences of TPMT alleles, resulting in low enzyme activity.…”
Section: *44mentioning
confidence: 99%
“…The most common and studied effect of SNPs found in TPMT are single amino acid substitutions disturbing TPMT enzyme structure and stability [105,187,188]. Decreased quantities of TPMT protein have often been the explanation for low enzyme activity of defective TPMT alleles [15] and correlations between protein amount and enzyme activity for most TPMT*1-13 have been reported [184].…”
Section: Biophysical Studies Of Low Activity Mechanismsmentioning
confidence: 99%